Productividad de los criaderos de Aedes aegypti en barrios de Medellín y Bello, Antioquia-Colombia (2011)
ABSTRACT: Dengue is a vector-borne viral disease. Aedes aegypti is the most important vector of Colombia and has shown that ecological flexibility, allows it to be adapted to different breeding sites, domiciliary and outdoors as buckets, pocetas, tanks, holes in trees, etc. OBJECTIVE To estimate the amount, positivity and productivity of Aedes aegypti deposits found in Santa Rita, Belén Rincón, Robledo Aures and París. MATERIALS AND METHODS We sampled 420 houses in four neighborhoods, searching for positive deposits of larvae and pupae of Ae. aeygpti between 2008 and 2010. We have quantified the number of breeding sites and we have performed a descriptive analysis and a non-parametric method to determine productivity. RESULTS There was found a difference among the deposits over the four districts. The most abundant deposit in the four districts was the pocetas. There was not significant difference found, between the productivity of the deposition of Santa Rita and Belén Rincón. There was found a significant difference between Robledo Aures and Paris’s deposits with a p<0.05, being the most productive tires and tanks respectively. CONCLUSIONS The amount, positivity and productivity of the deposits in the four districts had a different behavior, which indicates, that the dynamics of each district has to be known in order to establish the most indicated policies about the vector control. Key words: Aedes aegypti, Antioquia-Colombia, dengue, productivity, pupae breeding sites.